The Use of Ultra for the Safe Passage of the Anglo-American Expeditionary Forces to North Africa in 1942 - Brahim HAROUNI (Revue des Sciences Humaines)
In his book The Ultra Secret based on his war recollections the former British Intelligence Service Officer, Frederick  W. Winterbotham, revealed that the British cryptanalysts had, during the Second World War, broken the German most secret code used for communications between Berlin and German field commanders. ‘Ultra,’ the information derived from German enciphered messages, was sent out to British field commanders who could, in the light of often detailed information on their enemy’s strategy and tactic, mount their offensive or defensive actions. The British Intelligence Services had, however, remained absolutely silent on this question for about three decades after the war.